Legal Certainty of Interfaith Marriage in Relation to Civil Registration Legislation as an Effort to Develop Indonesian Marriage Law - Bunyamin Bunyamin (Journal of Social Research, 2026)
The enactment of Law No. 16 of 2019 concerning amendments to Law No. 1 of 1974 on Marriage represents a significant legislative development and addresses the need for uniform marriage legislation applicable to all Indonesian citizens. However, in practice, the implementation of this law continues to present legal challenges for certain segments of society, particularly those seeking to enter into interfaith marriages. This study employs a qualitative and descriptive-analytical approach, examining the issue of legal certainty in interfaith marriage in relation to civil registration legislation. The research adopts a normative juridical method, drawing upon the theories of the welfare state, justice, and legal development. Data analysis was conducted qualitatively, systematically, holistically, and comprehensively, incorporating a comparative analysis of interfaith marriage regulations in other countries. The findings of this study are as follows: (1) The issue of interfaith marriage in Indonesia under Law Number 16 of 2019, which amended Law Number 1 of 1974, is neither clearly nor definitively regulated; consequently, parties who intend to contract an interfaith marriage are left with limited options, namely marriage abroad, conversion to their partner's religion, or obtaining a judicial determination. (2) Interfaith marriage intersects with the civil registration function in Indonesia, whereby civil registration as the administrative mechanism for marriage recording does not itself confer legal validity upon a marriage, given that the validity of a marriage is ultimately governed by the religious law of each individual, in accordance with Article 2 Paragraph 1 of the Marriage Law, which stipulates that a marriage is legally valid only if it is solemnized in accordance with the religious law and beliefs of the parties concerned.